EFEKTIVITAS SELF CAREER EFFICACY TRAINING UNTUK MENURUNKAN KECEMASAN MASA DEPAN PADA MAHASISWA - Ramdani, Aulia; Wahyuni, Nur Fithriyah; Setyaningrum, Rantika; Rahmadani, Salwa Azzahra; Astaghits, Nasywa Rahmatika; Kusuma, Mochamad Arya Ramadhani; Mahardika, Akmal Riski (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
This study aims to see the effect of self-career efficacy training on student’s anxiety in facing the future. The research method uses an experimental quantitative approach. The data collection method used a future anxiety scale. The results showed that there was a difference in anxiety levels between before and after being given self-career efficacy training treatment with a value of p = 0.000 (p<0.05). Then the results of the study also showed that there was a difference in anxiety levels between the experimental group and the control group with a value of p = 0.036 (p<0.05). The results of this research are expected contribute to Mulawarman University as a basis for designing a more effective counseling program for students who experience future anxiety. Keyword: Future Anxiety, Self-career Efficacy, College Student